Magnesium depletion extends fission yeast lifespan via general amino acid control activation. Issue 2 (1st May 2021) - Ohtsuka, Hokuto; Kobayashi, Mikuto; Shimasaki, Takafumi; Sato, Teppei; Akanuma, Genki; Kitaura, Yasuyuki; Otsubo, Yoko; Yamashita, Akira; Aiba, Hirofumi
Abstract: Nutrients including glucose, nitrogen, sulfur, zinc, and iron are involved in the regulation of chronological lifespan (CLS) of yeast, which serves as a model of the lifespan of differentiated cells of higher organisms. Herein, we show that magnesium (Mg 2+ ) depletion extends CLS of the fission yeast Schizosaccharomyces pombe through a mechanism involving the Ecl1 gene family. We discovered that ecl1 + expression, which extends CLS, responds to Mg 2+ depletion. Therefore, we investigated the underlying intracellular responses. In amino acid auxotrophic strains, Mg 2+ depletion robustly induces ecl1 + expression through the activation of the general amino acid control (GAAC) pathway—the equivalent of the amino acid response of mammals. Polysome analysis indicated that the expression of Ecl1 family genes was required for regulating ribosome amount when cells were starved, suggesting that Ecl1 family gene products control the abundance of ribosomes, which contributes to longevity through the activation of the evolutionarily conserved GAAC pathway. The present study extends our understanding of the cellular response to Mg 2+ depletion and its influence on the mechanism controlling longevity. Abstract : Dietary restriction extends the lifespan of various model organisms, and the target nutrients are also diverse. Here, we show that Schizosaccharomyces pombe cells, especially the amino acid auxotrophic cells, sense the decrease of environmental magnesium level by activating the general amino acid control pathway and send the signal to Ecl1 family genes, which regulate the chronological lifespan via ribosomal regulation.